Impact of acute and chronic exposure to sulfamethoxazole on the kinetics and microbial structure of an activated sludge community - Pala-Ozkok, Ilke; Katipoglu-Yazan, Tugce; Olmez-Hanci, Tugba; Jonas, Daniel; Ubay-Cokgor, Emine; Orhon, Derin (Frontiers in Antibiotics, 2024)
The aim of this study was to reveal the microbial and kinetic impacts of acute and chronic exposure to one of the frequently administered antibiotics, i.e., sulfamethoxazole, on an activated sludge biomass. Respirometric analysis and model evaluation of the oxygen utilization rate profiles were the backbone of this study. The results showed that continuous exposure to sulfamethoxazole resulted in the inhibition of substrate storage and an increase in the endogenous decay rates by twofold, which was supported by analysis of the resistance genes. A mild inhibition on the growth and hydrolysis kinetics was also observed. Moreover, sulfamethoxazole had a binding impact with available organic carbon, resulting in a slightly less oxygen consumption. DNA sequencing and antibiotic resistance gene analyses showed that continuous exposure to sulfamethoxazole caused a change in the community structure at the species level. Resistant bacteria including Arthrobacter sp. and members of the Chitinophagaceae and Intrasporangiaceae families were found to have dominated the bacterial community. The impact of intermittent exposure was also investigated, and the results indicated a drop in the severity of the impact after 20 days of intermittence.